Applied EDI technologies in food traceability - Füzesi, István (Acta Agraria Debreceniensis, 2008)
Due to globalisation, the new technological developments and the complexity of food supply processes, the European food sector is increasingly becoming more complex. The consumers’ trust in food, triggered and affected by a number of food crises, is low. Today, consumers increasingly expect safe and high quality food and demand information about the origin of their food. Also, economic health of food industry can be greatly affected by food crises; therefore efficient and effective mechanisms are required to assist food industry in tracking and tracing products along the food chain. In this paper we discuss the criteria for efficient and effective traceability system from an IT perspective (mainly data exchange) and we identify key requirements for ICT enabled traceability.